Fish Species in a Changing World: The Route and Timing of Species Migration between Tropical and Temperate Ecosystems in Eastern Atlantic - Kaimuddin, Awaluddin H.; Laë, Raymond; Tito De Morais, Luis (Frontiers in Marine Science, 2016)
The presence of tropical species has been reported in Atlantic-European waters with increasing frequency in recent years. Unfortunately, the history of their migrations is not well understood. In this study, we examined the routes and timing of fish migrations in several ecosystems of the East Atlantic Ocean, combining several publicly available and unpublicized datasets on species occurrences. The species studied were those noted as exotic or rare outside their previous known area of distribution. We used sea surface temperature (SST) data obtained from 30 years of satellite observation to define three distinct time periods. Within these periods, temperature trends were studied in six ecosystems: the North Sea, the Celtic Sea, the South European Atlantic Waters, the Mediterranean Sea, the Canary Current and the Guinea Current. We also incorporated bathymetry data to describe the distribution of species. Measurement across a relatively large spatial extent was made possible by incorporating the capabilities of GIS. While SST increased consistently over time in all of the ecosystems observed, the change in number of species differed among ecosystems. The number of species in the middle regions, such as the South European Atlantic Shelf and the Western Mediterranean Sea, tended to increase over time. These regions received numbers of species from the lower or the upper latitudes according to season. Of all of the species observed in the recent period, 7 species from the Canary Current tended to be found in the Western Mediterranean Sea, and 6 species from these two regions extended their distributions to the South European Atlantic Shelf. Twelve species from the Canary Current moved seasonally to the Guinea Current. In the northern regions, 13 species moved seasonally in the North Sea and the Celtic Seas, and 12 of these species reached the South European Atlantic Shelf. This study presents a picture of routes and timing of species migration at the biogeographical scale. It shows how species have shifted their area of distribution (mostly northward) along the Eastern Atlantic ecosystems or have increased their depth ranges probably to remain within their preferred temperature range in response to long-term and seasonal environmental changes.